Negotiated justice and corporate crime : the legitimacy of civil recovery orders and deferred prosecution agreements /: the legitimacy of civil recovery orders and deferred prosecution agreements. (2018) - King, Colin (Colin Patrick), 1981-; Lord, Nicholas
No abstract available